Video Capsule Endoscopy After Bariatric and Gastric Surgery. Issue 1 (January 2015) - Stanich, Peter P.; Kleinman, Bryan; Porter, Kyle M.; Meyer, Marty M.
<x xml:space="preserve">Abstract</x> Goals: To investigate the outcomes of video capsule endoscopy (VCE) performed on patients after bariatric and gastric surgery with a focus on delivery method (oral ingestion or endoscopic placement). Background: There is minimal published data regarding the use of VCE in patients after bariatric and gastric surgery and the optimal delivery method is unknown. Methods: Retrospective case series of patients with bariatric or gastric surgery undergoing VCE in a tertiary care center over 3 years. Outcomes of interest were completion of the procedure and bowel transit times. Results: Twenty-three patients met study criteria. They underwent 24 VCE in the study period, with 13/16 (81.3%; 95% CI, 54%-96%) completed to the colon after oral ingestion and 5/8 (62.5%; 95% CI, 24%-91%) completed after endoscopic deployment. The median gastric transit time after oral ingestion was <1 minute (IQR, <1 to 99). Median total transit time after oral ingestion was 291 minutes (IQR, 213 to 434) and after endoscopic deployment was 364 minutes (IQR, 233 to >440) (P=0.48). There were no instances of capsule retention. Conclusions: Oral ingestion of VCE resulted in a satisfactory completion rate with rapid gastric transit after bariatric and gastric surgery. There were no capsule retention events. Given this and the favorable risk and cost profile, oral ingestion should be favored over endoscopic placement in this patient population.